The Brazilian comprehensive response to hepatitis C: from strategic thinking to access to interferon-free therapy - Fabio Mesquita; Melina Erica Santos; Adele Benzaken; Renato Girade Corrêa; Elisa Cattapan; Leandro Soares Sereno; Marcelo Contardo Moscoso Naveira (BMC, 2016)
Abstract Background Hepatitis C affects over 185 million people around the world. This silent disease is responsible for up to 700,000 deaths per year. Despite the scientific revolution in diagnosis and treatment, hepatitis C control remains a huge challenge due to the cost of effective medications. In response to the global outcry of hepatitis epidemic and the need to improve the nation's public health response, the Ministry of Health of Brazil revolutionized hepatitis C treatment by incorporating highly effective drugs that can be accessed through sustainable and universal means. Discussion This paper describes the unique process of implementing evidence-informed policy to respond to hepatitis C epidemic through the update of hepatitis C treatment in Brazil based on the estimate of disease prevalence, current international guidelines, and the cost-effectiveness impact in the Brazilian Unified Health System. Through a debate of an experience report, the authors underlie the strategic plan implemented according to the situation analysis that emphasized the need to improve its current response over a relatively short-term period. The comprehensive response is detailed comprising three main objectives: improve treatment outcomes by evaluating and incorporating new and effective medications at a sustainable price; elaborate on clinical guidelines to treat hepatitis C patients; and develop awareness and diagnosis campaigns targeted at the population of interest. In this scenario, Brazil was able to obtain an unprecedented discount for a high-medium income country; provided treatment to more than 7000 individuals in the last 2 months of 2015; and expects to treat 38,000 new patients in 2016. Summary The remarkable process applied in Brazil was developed according to epidemiological data and scientific evidence, and it was motivated by the engagement of the country in the Sustainable Development Goals, which may inspire other developing countries to identify ways to achieve these goals by 2030.